Analysing the process of creating unstable situations in football - Kim, H.; James, N.; Parmar, N.; Rees, G. D.; Vuckovic, G. (World Congress of Performance Analysis of Sport XII, 2018)
Purpose: For a complex sport where players use off-the-ball positioning to gain an advantage over their opponents It may be difficult to discern periods of stability and instability and furthermore which actions are responsible for changes in the system state. Whilst previous papers have attempted to identify perturbations, there were no operational definitions for stability, instability or perturbations with consequent subjectivity for determining these events. The main aim of this study was to identify the process of creating unstable situations in football. Method: This study established operational definitions for 5 Perturbation chances (Midfield line break, Zone 14, Wide area, Counter attack and Set piece) when a team had an advantage and Perturbation attempts (Attempt- short pass, long pass, dribble or skill, quick movement, cross, shot and No attempt- lost possession, switch chance, out of chance, time wasting). Also, unstable situations were categorised into 5 situations, deemed unstable (Penalty box possession, Counter attack, Ratio attacking to defending player, Successful cross and Shot). Result: A total of 81.5 perturbation chances occurred, resulting in 44.5 attempts and 23.5 successes (unstable situations) per team per match. Of 81.5 perturbation chances, 31.1% were wide area chances (M= 28.5), which was the highest, but led only to 14 attempts and 7 unstable situations whilst set piece chance had great efficiency (6 chances led to 6 attempts and 4 unstable situations). A team created more unstable situations by approaching penalty area (M= 9.5) than cross (M= 6) or counter attack (M= 5.5). Conclusion: Analysing the whole process of perturbations takes more holistic view and dynamically considers the sequential dependency of different events. This study seeks to adopt a methodology that facilitates the discovery of perturbations, which can be more idiographic than previous nomothetic approaches.